Use of abbreviations in the nursing records of a teaching hospital - Sylvia Miranda Carneiro; Herica Silva Dutra; Fernanda Mazzoni da Costa; Simone Emerich Mendes; Cristina Arreguy-Sena (Universidade Federal do Ceará, 2016)
Objective: to evaluate the use of abbreviations in nursing records of a teaching hospital and describe their profile in different sectors, work shifts and professional nursing categories. Methods: documentary study that analyzed 627 nursing records in 24 patient charts using a systematic observation script. Results: we identified 1,792 abbreviations, and 35.8% were nonstandard. The incidence of abbreviations was higher in the Intensive Care Unit, used by nurses and in the night shift. Conclusion: abbreviations are part of the day-to-day of nursing records. The use of nonstandard abbreviations make difficult to understand the records content, can generate misinterpretations, put at risk the users' safety and impair the continuity of labor work.